Analisis Pendapatan Dan Pola Konsumsi Petani Kelapa Sawit Di Desa Sumber Makmur Kecamatan Tapung Kabupaten Kampar - Wulandari '; Rita Yani Iyan; Dahlan Tampubolon (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to find out how farmers income and how palm farmer consumption patterns at Desa Sumber Makmur. Research on the method of use is Random Sampling. Site selction research for an avarage population of livelihood as farmers edged palm. Using primary data and secondary data obtained through interviews in the palm growers and retrieved data information from relevant agencies such as the office of the Sumber Makmur village. The results showed that the income of the farmers in the Sumber Makmur village of palm in 2013 on avarage by Rp. 5.269.412,- and consumption patterns of palm farmers greater fulfilment of the non food consumption from the consumption of food. This show that the income received by farmers in the Sumber Makmur village palm already able to meet the needs of their household.Keyword : analysis of farmers income, consumption of food and non food.